(untitled) (Microbes and Health, 2016)
Mycobacterium avium subspecies paratuberculosis (MAP) is the etiological agent of chronic enteric disease of ruminant known as paratuberculosis (Johne’s disease). The disease causes considerable economic losses worldwide due to reduced milk production and eventually, diarrhoea, weight loss and death. Johne’s disease (JD) has some pathological similarities with Crohn’s disease (CD) in humans, and the role of MAP in the causation of CD has been under investigation for last 100 years. Animals infected with JD shed viable MAP in the blood, and tissues. Consequently, transmission to humans may occur via consumption of animal derived foods. In developing countries, limited information is available on the occurrence of MAP infection in animals and humans. MAP infection has been established in animals and humans may get the MAP exposure through food chain or contaminated environment. Presently, MAP is of great public health significance because it is speculated to be involved in Crohn’s disease in humans. The present review summarizes the information primarily on the nature of MAP in animals and humans, economic losses and morbidity and mortality due to JD and CD at global level. Current concept on the possible relationship between MAP and Crohn’s disease has also been reviewed. Microbes and Health, January 2015. 4(1): 4-13